Effect of fermented cassava (Manihot esculenta Crantz) on maternal development and fetal teratogenicity in mice (Mus musculus L.) - Sukmadani Rusdi, Mesa; Novrianti, Silda; Hasanah, Nur; Efendi, M. Rifqi; Armenia, Armenia (Science, Engineering and Health Studies, 2023)
Fermented cassava (Manihot esculenta Crantz) is one of the traditional foods favored by the community, including pregnant women, but it has been reported to have various adverse effects. Therefore, this study aimed to analyze the effect of fermented cassava on maternal development and fetal teratogenicity in mice (Mus musculus L.). A total of 36 pregnant female white mice were divided into three main groups representing different pregnancy periods (first, second, and third). Each main group was subdivided into four subgroups, including a control group and three treated groups. The treated groups received doses of 0.075 g/kg, 0.15 g/kg, and 0.3 g/kg body weight of fermented M. esculenta Crantz. Furthermore, the treatment was orally administered for five consecutive days, with daily measurements of maternal body weight. On the 18th day of pregnancy, mice were laparatomized to evaluate the morphological and skeletal teratogenic effects of fermented cassava on the fetus. Statistical analysis of maternal body weight, number of fetuses, and fetal body weight during pregnancy was conducted. The administration of fermented cassava significantly affected maternal body weight. The results showed that there was no significant difference between the number of fetuses and fetal body weight. However, the intake of fermented cassava in a dose-dependent manner tended to reduce the number of fetuses and fetal weight, compared to the control group in all gestation periods. Based on the results, fermented cassava exhibited a potential teratogenic effect on certain fetuses, leading to spontaneous abortion and fetal death in all treated groups and gestation periods, particularly in the second period. Therefore, its consumption is deemed unsafe and must be prohibited for pregnant women.